Evaluation of Moisture Regime on Agronomic Traits of Rice Genotypes (Annals of Bangladesh Agriculture, 2022)
Drought stress is a major constraint to the production and yield stability of crops. Rice (Oryza sativa L.) is one of the most important cereals and considered as a drought sensitive crop species. A field experiment was conducted in the vinylhouse of the Department of Agronomy, Bangabandhu Sheikh Mujibur Rahman Agricultural University, Bangladesh, during March - August 2018 to evaluate the performance of 38 rice genotypes under control and drought conditions. The experiment was laid out in a completely randomized design containing two water regimes with three replications. The water regimes were well-watered and induced moisture stress conditions. Multivariate and principal components analyses revealed that different plant characters, viz. plant height, total tillers hill-1, panicle number hill-1, length of panicle, filled grains panicle-1, 1000-grain weight, grain yield plant-1 and straw weight plant-1 showed a wide range of variation due to variation in moisture level. Correlation study and biplot analysis considering PC1 and PC2 explained that grain yield was positively correlated with filled grain panicle-1, total tiller hill-1, panicle number hill-1 and 1000-grain weight. Based on the grain yield plant-1 (g) and others agronomic characters, the genotypes BU Acc 33 (26.68 g), BU Acc 30 (21.81 g), and BU Acc 21 (20.58 g) were identified as promising genotypes for developing drought tolerant variety (ies).Ann. Bangladesh Agric. (2021) 25 (1) : 89-104